Self-Directed Learning Model: Communication, Collaboration, Critical Thinking, Creativity (4C) Skills for Elementary School Students - Nurul Fachriyah; Abdul Wahid; Syarifah Nur Fajrin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The challenges of modern education demand mastery of 21st-century skills (4Cs), but their implementation is often hampered by conventional learning patterns that have not been able to stimulate student independence. This study aims to analyze the application and influence of the Self-Directed Learning (SDL) model on Communication, Collaboration, Critical Thinking, and Creativity (4Cs) skills in fourth-grade students at Elementary School Inpres Paccerakkang, Makassar City. The method used is quantitative with a pre-experimental design, involving a sample of 29 students selected through a saturated sampling technique. The results of the study indicate that the application of the SDL model is effective in creating an active learning atmosphere and increasing student motivation. Furthermore, the hypothesis test shows a significant influence of the SDL model on 4Cs skills with a significance value of 0.00 < 0.05. This proves that the independent learning approach is empirically able to improve students' integrative abilities. Practically, this research contributes to educators implementing innovative student-centered strategies, as well as being a strategic reference for schools to produce graduates who are adaptive to the demands of the times through developing independent learning from an early age.